Relationship between birth weight and adult lung function: controlling for maternal factors. Issue 12 (26th November 2003) - Edwards, C A; Osman, L M; Godden, D J; Campbell, D M; Douglas, J G
Abstract : Background: There is conflicting evidence on the "fetal origins hypothesis" of association between birth weight and adult lung function. This may be due to failure to control for confounding maternal factors influencing birth weight. In the present study access to birth details for adults aged 45–50 years who were documented as children to have asthma, wheezy bronchitis, or no respiratory symptoms provided an opportunity to investigate this association, controlling for maternal factors. Methods: In 2001 the cohort was assessed for current lung function, smoking status, and respiratory symptoms. Birth details obtained from the Aberdeen Maternity and Neonatal Databank recorded birth weight, gestation, parity, and mother's age and height. Results: 381 subjects aged 45–50 years were traced and tested for lung function; 323 (85%) had birth details available. A significant linear trend (p<0.01) was observed between birth weight and current forced expiratory volume in 1 second (FEV1 ) and forced vital capacity (FVC) values (adjusted for height, age, sex, weight, deprivation category (Depcat), childhood group, and smoking status). This trend remained significant after adjusting birth weight for gestation, parity, sex, mother's height and weight (p = 0.01). The relationship between birth weight and FEV1 and FVC remained significant when adjusted for smoking history. There was no association between birth weight and current wheezing symptoms. Conclusion: There is a positive linear trend between birth weight, adjusted for maternal factors, and lung function in adulthood. The strength of this association supports the "fetal origins hypothesis" that impairment of fetal growth is a significant influence on adult lung function.